1994
DOI: 10.1148/radiology.193.2.7972746
|View full text |Cite
|
Sign up to set email alerts
|

Lung changes in rheumatoid arthritis: CT findings.

Abstract: CT may be a useful noninvasive tool for recognition of RA-associated lung disease with special emphasis on bronchial and bronchiolar changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
3
17

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(134 citation statements)
references
References 0 publications
6
108
3
17
Order By: Relevance
“…Modern studies have found symptomatic bronchiectasis with a prevalence of 2.7% in RA subjects, compared to 0.03% in the general population 2 . High resolution computed tomography (HRCT) studies demonstrate the prevalence to be much higher, with radiological BR in RA populations repeatedly reported in the region of 30% [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Modern studies have found symptomatic bronchiectasis with a prevalence of 2.7% in RA subjects, compared to 0.03% in the general population 2 . High resolution computed tomography (HRCT) studies demonstrate the prevalence to be much higher, with radiological BR in RA populations repeatedly reported in the region of 30% [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Differential diagnosis of exudative pleural effusion with low pH, low glucose and high LDH includes bacterial empyema, tuberculosis, malignancy, paragonimiasis and rheumatoid pleurisy (6,7). RA related pleural effusion is expected to have low glucose (<20 mg/dL), complement levels, LDH levels of >1000 U/L and pH of <7.00 (7)(8)(9)(10)(11)(12). Pleural fluid glucose to serum glucose rate was found below 0.5 in 80% of the RA patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…El TACAR de control a las 10 semanas informó de mejoría radiológica. En la NO la TAC torácica muestra las características opacidades subpleurales en vidrio deslustrado 8 . El diagnóstico definitivo es histopatológico, en la mayoría de casos por biopsia transbronquial o videotoracoscopia, demostrándose fibroblastos en los bronquiolos y alvéolos 9 .…”
Section: Discussionunclassified